Dynamic regimes of cyclotron instability in the afterglow mode of minimum-B electron cyclotron resonance ion source plasma. (22nd February 2016) - Mansfeld, D; Izotov, I; Skalyga, V; Tarvainen, O; Kalvas, T; Koivisto, H; Komppula, J; Kronholm, R; Laulainen, J
Abstract: The paper is concerned with the dynamic regimes of cyclotron instabilities in non-equilibrium plasma of a minimum- B electron cyclotron resonance ion source operated in pulsed mode. The instability appears in decaying ion source plasma shortly (1–10 ms) after switching off the microwave radiation of the klystron, and manifests itself in the form of powerful pulses of electromagnetic emission associated with precipitation of high-energy electrons along the magnetic field lines. Recently it was shown that this plasma instability causes perturbations of the extracted ion current, which limits the performance of the ion source and generates strong bursts of bremsstrahlung emission. In this article we present time-resolved diagnostics of electromagnetic emission bursts related to cyclotron instability in the decaying plasma. The temporal resolution is sufficient to study the fine structure of the dynamic spectra of the electromagnetic emission at different operating regimes of the ion source. It was found that at different values of magnetic field and heating power the dynamic spectra demonstrate common features: Decreasing frequency from burst to burst and an always falling tone during a single burst of instability. The analysis has shown that the instability is driven by the resonant interaction of hot electrons, distributed between the electron cyclotron resonance (ECR) zone and the trap center, with slow extraordinary wave propagation quasi-parallel with respect to the external magnetic field.